2013
DOI: 10.1177/0897190013491768
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Pharmacy Student and Resident-Led Discharge Counseling on Heart Failure Patients

Abstract: There was no statistically significant difference in readmission rates; however, several medication errors were prevented, and a large percentage of patients expressed an improved understanding of their medications.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
51
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 42 publications
(53 citation statements)
references
References 23 publications
2
51
0
Order By: Relevance
“…Similar to what was observed in the study by Szkiladz et al, 6 we did not find that pharmacy student involvement helped decrease hospital readmission rates. Because readmissions and medication nonadherence are common among mental health patients, we wanted to help decrease these phenomena through the pharmacy students' rotation in the inpatient mental health unit.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Similar to what was observed in the study by Szkiladz et al, 6 we did not find that pharmacy student involvement helped decrease hospital readmission rates. Because readmissions and medication nonadherence are common among mental health patients, we wanted to help decrease these phenomena through the pharmacy students' rotation in the inpatient mental health unit.…”
Section: Discussionsupporting
confidence: 92%
“…5 In addition to medication reconciliation, pharmacy students have demonstrated that they are capable of providing high-quality discharge counseling, therapeutic recommendations, and cost avoidance. 3,[6][7][8] To date, only one study has evaluated the cost-saving potential of pharmacy students' clinical interventions in a psychiatric hospital. 8 We studied the effect of medication reconciliation by pharmacy students in an inpatient mental health facility.…”
Section: Resultsmentioning
confidence: 99%
“…As part of our practice model, pharmacists, residents, and students perform specialized counseling to all patients with CHF, chronic obstructive pulmonary disease, acute myocardial infarction, or pneumonia; however, there is little evidence that such counseling reduces 30-day readmissions. Szkiladz et al 13 utilized students and residents to perform discharge counseling for patients with CHF but did not find a reduction in 30-day CHF readmission rates when compared with standard discharge counseling. However, the authors did see a reduction in medication errors that resulted in significant cost avoidance for the institution and found that patients demonstrated an improved understanding of their medications.…”
Section: Discussionmentioning
confidence: 97%
“…Multiple studies documented the impact of pharmacist‐delivered transition of care programmes on 30‐day readmissions, ED visits and quality of life. These studies used a variety of research approaches including randomized design [14,15], prospective [9] and retrospective cohorts studies [10,17,20]. Holland et al .…”
Section: Discussionmentioning
confidence: 99%